Bat algorithm based control to decrease the control energy consumption and modified bat algorithm based control to increase the trajectory tracking accuracy in robots - Rubio, José de Jesús (Neural networks, 2023)
From the control theory, the best control gain produces a balance between the trajectory tracking accuracy and control energy consumption. The random search of the bat algorithm is one alternative to find the best control gain. In this paper, (1) a bat algorithm based control is proposed to decrease the control energy consumption in robots, where a bat algorithm is used to find the best control gain; and (2) a modified bat algorithm based control is proposed to increase the trajectory tracking accuracy in robots, where a modified bat algorithm is used to find the best control gain. The comparison between the two proposed controls and the simplex based control is illustrated for the trajectory tracking accuracy and control energy consumption in two robots. •A bat algorithm based control is proposed to decrease the control energy consumption in robots, where a bat algorithm is used to find the best control gain.•A modified bat algorithm based control is proposed to increase the trajectory tracking accuracy in robots, where a modified bat algorithm is used to find the best control gain.•The comparison between the two proposed controls and the simplex based control is illustrated for the trajectory tracking accuracy and control energy consumption in two robots.